Expectations of inflations: The biasing effect of thoughts about specific prices - Wändi Bruine de Bruin; Wilbert van der Klaauw; Giorgio Topa (Federal Reserve Bank of New York, 2011)
National surveys follow consumers' expectations of future inflation, because they may directly affect the economic choices they make, indirectly affect macroeconomic outcomes, and be considered in monetary policy. Yet relatively little is known about how individuals form the inflation expectations they report on consumer surveys. Medians of reported inflation expectations tend to track official estimates of realized inflation, but show large disagreement between respondents, due to some expecting seemingly extreme inflation. We present two studies to examine whether individuals who consider specific price changes when forming their inflation expectations report more extreme and disagreeing inflation expectations due to focusing on specific extreme price changes. In Study 1, participants who were instructed to recall any price changes or to recall the largest price changes both thought of various items for which price changes were perceived to have been extreme. Moreover, they reported more extreme year-ahead inflation expectations and showed more disagreement than did a third group that had been asked to recall the average change in price changes. Study 2 asked participants to report their year-ahead inflation expectations, without first prompting them to recall specific price changes. Half of participants nevertheless thought of specific prices when generating their inflation expectations. Those who thought of specific prices reported more extreme and more disagreeing inflation expectations, because they were biased toward various items associated with more extreme perceived price changes. Our findings provide new insights into expectation formation processes and have implications for the design of survey-based measures of inflation.
Keywords: E31; D84; 330; inflation expectations; perceptions of specific prices; memory bias; recall; Inflationserwartung